PENGARUH KREATIVITAS DAN GAYA BELAJAR TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X MA DDI CITTA KABUPATEN SOPPENG - Musdalifah Musdalifah; Sumarni Sumarni (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to determine the effect of creativity and learning style on economic learning outcomes of class X MA DDI Citta students, Soppeng Regency. This type of research is correlational and expost facto research with a quantitative approach. The population in this study amounted to 216 students while the sample was 81 people. The results of the study showed that class X MA DDI Citta Soppeng Regency had high creativity as much as 93.83%, learning styles by 82.94%, and learning outcomes as much as 69.13%. The simultaneous effect of creativity and learning style on students' economic learning outcomes shows that there is a positive and significant effect, this is shown through the results of simultaneous testing (F test), because the significance value is 0.00 <0.05. The effect of creativity on economic learning outcomes for students of class X MA DDI Citta shows that partially the creativity variable (X1) has an effect on economic learning outcomes (Y), this is indicated by a significance value of 0.00 <0.05. The effect of learning style on economic learning outcomes of MA DDI Citta students shows that partially the learning style variable (X2) has an effect but is not significant on economics learning outcomes (Y), this is indicated by a significance value of 0.881 > 0.05.